The local impact of the International Criminal Court: from law to justice - Wierda, Marieke (Cambridge University Press, 2023)
The International Criminal Court seeks to end impunity for the world's worst crimes, to contribute to their prevention. But what is its impact to date? This book takes an in-depth look at four countries under scrutiny of the ICC: Afghanistan, Colombia, Libya, and Uganda. It puts forward an analytical framework to assess the impact of the ICC on four levels: on the domestic legal systems (systemic effect); on peace negotiations and agreements (transformative effect); on victims (reparative effect); and on the perceptions of affected populations (demonstration effect). It concludes that the ICC is having a normative impact on domestic legal systems and peace agreements, but it has brought little reparative justice for victims, and it does not necessarily correspond with how affected populations view justice priorities. The book concludes that justice for the world's worst crimes has no 'universal formula' that can easily be captured in law by one institution.